Effects of hydroquinone and gelatin on the electrodeposition of Sn–Bi low temperature Pb-free solder - Goh, Y.; Haseeb, A.S. Md. Abdul; Sabri, Mohd Faizul Mohd (Elsevier, 2013)
The effects of an antioxidant, hydroquinone (HQ) and a grain refining additive, gelatin, on the electroplating characteristics of Sn–Bi alloys were investigated. Methane sulfonic acid (MSA) based plating baths with varying contents of additives were prepared and the electrochemical behavior of each bath was investigated. The combination of HQ and gelatin successfully reduces the deposition potential gap between the elements hence facilitates the co-deposition of Sn–Bi in this plating bath. Compact, adherent deposits could be obtained through the synergistic effects of these two additives. The electroplated Sn–Bi deposits showed a decrease in Bi content with increasing current density. Near eutectic Sn–60.75 wt.% Bi alloy was successfully deposited from the bath containing both HQ and gelatin at a current density of 18 mA cm−2.